Unveiling a hidden threat: whole genome sequencing exposes the cross-hospital spread of extensively drug-resistant Pseudomonas aeruginosa - Kamau, Edwin; Jones, Brendan; Kitjawat, Tatdanai; Youn, Han Ha; Schweikert, Michael J.; Caldwell, Angela; Harens, Christopher; Kiernan, Patrick T.; Velasco, John Mark; Lebreton, Francois; Copeland, Nathanial K. (Frontiers in Microbiology, 2026)
IntroductionWhole genome sequencing (WGS) was performed on 10 extensively drug-resistant (XDR) Pseudomonas aeruginosa ST235 isolates to investigate potential healthcare-associated transmission of XDR P. aeruginosa ST235 within a U.S. military treatment facility (MTF), assess its environmental persistence, and determine its genomic relatedness to global strains.MethodsPatient samples were collected and processed using standard clinical protocols. To assess potential environmental contamination, ICU sink drains from rooms previously occupied by study patients were swabbed, cultured in BHI and BAP media, and screened by PCR targeting 16S rRNA and P. aeruginosa ecfX. Isolates included 2 from the index patient with prior hospitalization in the Philippines, 4 from a secondary patient in the same ICU, and 4 from the index patient’s room sink collected 9 months later. Genetic relatedness was evaluated using core genome multilocus sequence typing (cgMLST) and single nucleotide polymorphism (SNP) analysis. Antimicrobial resistance genes were identified with AMRFinderPlus, and global phylogenetic comparisons were performed using publicly available genomes from NCBI and the MRSN database.ResultsThe 6 clinical isolates differed by only 0–4 SNPs, indicating high genetic relatedness. The 4 environmental isolates differed from the clinical isolates by just 1 allele in cgMLST and 0–4 SNPs. Global phylogenetic analysis showed close clustering with ST235 strains from the Philippines, with the closest match being a 2018 Manila isolate (1–12 allele differences). The isolates carried the blaVIM-2 carbapenemase gene and exhibited resistance to all tested antibiotics.DiscussionWGS surveillance revealed an undetected intra-hospital transmission of XDR P. aeruginosa ST235 and its persistence in the environment for at least nine months. The findings underscore the importance of genomic surveillance in identifying AMR outbreaks, especially among patients returning from high-risk regions, and proactive infection control measures to prevent the spread of high-risk AMR clones in healthcare settings.